ABA SOUTH EMPLOYERS’ ASSESSMENT OF EMPLOYEES LANGUAGE AND COMMUNICATION SKILLS: THE CASE OF ABA METROPOLIS - M. Chukwu, Ebere; Onyekwere , Okpara; Ngozi Ewurum , Rosecolette (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
This paper examines how employers of labour in Aba metropolis view their employees’ language and communication skills. The paper adopts Human Capital Theory to assess language and communication skills and its potency in Nigeria labour market. Data for analysis were elicited through a structured questionnaire to one hundred employers of labour in Aba South Local Government Area selected by purposive sampling technique. This is necessary as research studies on the level of employability of Nigerian graduates show that language and communication skill top the list of the skills requisite for advancement of employability. Results from data analysis show that about 50% of the respondents were of the view that their employees lacked good communication skills while about 70% said their workers lacked the language specific to their profession. More than 50% of the respondents agreed that their employees’ communication skills advance attainment of their organisational goals while about 40% of them disagreed to it. Most importantly, 100% of the respondents said they would not employ candidates that lacked communication skills. The paper, therefore, concludes that lack of good communication skill is one of the problems that advance youth unemployability in Nigeria.